Dry deposition velocity of 137Cs and 134Cs in Spain after the Fukushima Dai-Ichi Nuclear Power Plant accident. (March 2016) - Vargas, A.; Camacho, A.; Laubenstein, M.; Plastino, W.
Abstract: Aerosol samples collected at the Technical University of Catalonia in Barcelona were analysed for traces of 134 Cs and 137 Cs emitted during the Fukushima Dai-ichi Nuclear Power Plant accident in March 2011. Samples were collected with a high-volume airborne particulate sampling system, and with a dry and wet deposition collection system for subsequent analysis. Due to the very low activities, the filters were measured in an underground ultra-low background laboratory. This has enabled the characterization of dry velocity deposition for 134 Cs and 137 Cs. Results show a dry velocity deposition of 0.07 cm s −1 . Highlights: Dry deposition velocity of 134 Cs and 137 Cs in Barcelona emitted from Fukushima accident. High-volume air sampler used for radioactive aerosol concentration measurement. Deposition flux was calculated using an automatic deposition sampler. Filters have been measured in an ultra-low background laboratory.